L’archange des commencements - Tereza Sinigalia (Anastasis: Research in Medieval Culture and Art)
The restoration of the mural paintings in the Church of Saint Nicholas, Rădăuţi, which has just been achieved, shows new light on an iconographic ensemble devoted to Archangel Michael. The author relates these paintings to the dedication of the first church in Rădăuţi, built in oak wood, predating the reign over Moldavia of Bogdan Ist of Maramures, of his son Lațcu and the boyar Costea, husband of Margareta/ Mușata, mother of Petru Ist and of Roman Ist. Petru is the founder of the church in stone, the only one to survive. In both churches were buried Moldavia’s voivodes of the second half of the fourteenth century. In sign of deep veneration toward his ancestors, Stephen the Great had Mistr Jan carve their tombstones in 1479 – 1480, when the inside of the church was also painted. It is at the same epoch that the higher narthex of the Saint Nicholas church was constructed. The hagiographic cycle is made up of 25 sequences, either entirely or partially conserved. Most of them are inspired by the Old Testament, one by the New Testament, two by the scenes of the Archangel’s miracle at Chonae, and two others by historically attested characters – emperors Constantine the Great and Justinian. Apart from this rich iconography with its outstanding illustrations, the ensemble was the work of an exceptionally gifted painter, whose style was remarkably refined.